Wali mujbir perspektif Undang-undang No. 1 Tahun 1974 dan hukum islam - Syafii , Imam; Hariati, Nina Agus (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2023)
Marriage is an important thing in the reality of human life. With marriage, households can be upheld and fostered in accordance with religious norms and community life. According to Law Number 1 of 1974, the definition of marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on God Almighty. According to the opinion of the Shafi'iyah scholars, a marriage is not valid without a guardian for the woman, while for men no guardian is needed. The author uses normative qualitative methods with library research data collection methods to obtain data in this study. Based on the results of the research, it can be concluded that the position of the mujbir guardian in Islamic marriage law is based on considerations for the good of the girl being married, because it often happens that a girl is not good at choosing her soul mate appropriately. If the girl is released to choose her own mate, it is feared that it will bring harm to the girl herself in the future, for example in terms of religious maintenance, and so on.